A DESCRIPTIVE STUDY ON SUBTITLING STRATEGIES OF CULTURE-SPECIFIC ITEMS (CSIS) IN THE DOCUMENTARY FILM ENTITLED “THE MARK OF EMPIRE MAJAPAHIT - Soimatul Fitriani; Nur Hasibin; Arin Inayah (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
Subtitling is written translations from the source language to the target language, which are positioned at the bottom of the screen that appear and disappear along with the dialogue in the film. Translators often find difficulties in translating subtitles contains many cultural terms (culture-specific items/CSIs). CSIs are culturally specific concepts that do not exist in other cultures. Therefore, the researcher chose to analyze CSI by taking object from Peter Lee's documentary film entitled “The Mark Of Empire Majapahit”. The research method used is descriptive qualitative. The purpose of this study was to find out the strategy of CSI and subtitling strategies of CSIs in the documentary film of “The Mark of Empire Majahpahit